Metal oxide semiconductors for dye degradation. (December 2015) - Adhikari, Sangeeta; Sarkar, Debasish
Graphical abstract: Highlights: Hydrothermal synthesis of monoclinic and hexagonal WO3 nanostructures. Nanocuboid and nanofiber growth using different structure directing agents. WO3 –ZnO nanocomposites for dye degradation under UV and visible light. High photocatalytic efficiency is achieved by 10 wt% monoclinic WO3 . WO3 assists to trap hole in UV and arrests electron in visible light irradiation. Abstract: Organic contaminants are a growing threat to the environment that widely demands their degradation by high efficient photocatalysts. Thus, the proposed research work primely focuses on the efficient degradation of methyl orange using designed WO3 –ZnO photocatalysts under both UV and visible light irradiation. Two different sets of WO3 nanostructures namely, monoclinic WO3 (m-WO3 ) and hexagonal WO3 (h-WO3 ) synthesizes in presence of a different structure directing agents. A specific dispersion technique allows the intimate contact of as-synthesized WO3 and ultra-violet active commercial ZnO photocatalyst in different weight variations. ZnO nanocrystal in presence of an optimum 10 wt% m-WO3 shows a high degree of photocatalytic activity under both UV and visible light irradiation compared to counterpart h-WO3 . Symmetrical monoclinic WO3 assists to trap hole in UV, but electron arresting mechanism predominates in visible irradiation. Coupling of monoclinic nanocuboid WO3 with ZnO proves to be a promising photocatalyst in both wavelengths.